Study on change law of time function parameters for dynamic prediction of mining subsidence: Taking Weibull as an example - Chenglin YU; Hongzhen ZHANG; Hongdong FAN (Meikuang Anquan, 2024)
In view of the fact that the time function parameters in the dynamic prediction model of mining subsidence are mainly obtained by inversion based on the subsidence time series of the maximum subsidence point, its research on the spatial position change law above the working face is insufficient. According to the stress and collapse of the overburden during the advancing process of the working face, the goaf is divided into three sections in the plane direction: vertical overall compression zone, middle zone and dynamic full zone; taking Weibull time function as an example, the meaning, spatial distribution law and characteristics of the parameters m and k of dynamic prediction are analyzed, and the partition mathematical model and selection criteria of the two parameters are constructed; based on the measured final value and the predicted value of probability integral method, the correctness is verified through examples, which enriches the research on parameters of mining subsidence dynamic prediction.